Examining the Relationship between School Climate and Achievement Goals among High School Students - Nur Sholehah Dian Saputri; Muhammad Luthfi; Luky Kurniawan (Borneo Research and Education Center, 2026)
Students’ achievement goals are shaped by various internal and external factors, including the school climate, which influences academic motivation. This study aimed to examine the relationship between school climate and achievement goals among senior high school students. A quantitative correlational design was employed, involving 126 tenth-grade students selected through random sampling. Data were collected using questionnaires measuring school climate and achievement goals. Prior to hypothesis testing, assumption tests were conducted. The Kolmogorov–Smirnov test indicated that the data were normally distributed (p = 0.200), and the linearity test confirmed a linear relationship between the variables (p < 0.05). Pearson’s product-moment correlation analysis revealed a positive and statistically significant relationship between school climate and achievement goals (r = 0.494, p < 0.001), indicating a moderate correlation. The coefficient of determination showed that school climate accounted for 24.4% of the variance in students’ achievement goals. These findings suggest that a supportive and positive school climate is moderately associated with stronger achievement goal orientation among students. The study underscores the importance of fostering a conducive school environment to support the development of students’ academic goals.